Inflatable L-shaped prisms as soft actuators for soft exogloves. (15th October 2019) - Jung, Ju Cheol; Jang, Jae Hyuck; Rodrigue, Hugo
Abstract: Soft pneumatic bending actuators generally produce a bending deformation through pressurization, but the force they produce diminishes significantly throughout the deformation for a given pressure level. This is useful to produce a controlled motion, but sensors are required to enable force control of the actuator throughout this motion. This paper introduces the use of an inflatable L-shaped prism as a soft actuator that has a constant equilibrium angle and produces a fairly constant force throughout most of its actuation range. This combination of characteristics makes the actuator ideal for applications where an easily controllable force without the use of sensors is required or preferable. However, it is unsuitable for applications where motion control is necessary due to its constant equilibrium angle. The effect of different geometric parameters and materials were tested, and it was found that this actuator could produce a blocked force of up to 13 N at 80 kPa and could maintain this force throughout most of this range of motion. This actuator concept was then used to build a three-fingered soft exoglove capable of grasping a wide range of objects.